An Injection-Locked Single-Longitudinal-Mode Fiber Ring Laser With Cylindrical Vector Beam Emission - Hongdan Wan (IEEE Photonics Journal, 2017)
We demonstrate a fiber ring laser with narrow bandwidth single-longitudinal-mode cylindrical vector beam (CVB) output at C-band wavelength range for the first time to the best of our knowledge. A step index two-mode fiber Bragg grating is used as a transverse mode selector for CVB generation, while both the injection-locking technique and narrow bandwidth of the fiber Bragg grating lead to single-longitudinal-mode operation. The 3-dB bandwidth of the laser output is measured to be <;0.01 nm near a single wavelength of 1551.4 nm with a signal-to-background ratio of >60 dB. Mode distribution and optical spectra of few-mode fibers with periodic modulated refractive index profile, namely the few-mode fiber Bragg gratings with bent radius, are investigated theoretically and experimentally, which provide a comprehensive exploration of CVB's generation.